trans Activation of the simian virus 40 late transcription unit by T-antigen. - Brady, J (1985)
We have investigated the role of simian virus 40 (SV40) T-antigen in the induction of late gene expression independent of its function in amplifying templates through DNA replication. Northern blot and S1 nuclease analyses showed that stimulation occurred at the transcriptional level. At least two template elements, the T-antigen-binding sites and the 72-base-pair repeats, appeared to be important for this induction. Using template mutants, we demonstrated that deletions within T-antigen-binding site II decreased T-antigen-mediated late gene expression approximately 10- to 20-fold. In addition, multiple point mutations within a single retained copy of the SV40 72-base-pair repeat decreased T-antigen-mediated late gene expression. Using in vivo competition studies, we demonstrated that competitor DNA fragments containing the SV40 control region (nucleotides 5171 through 272) quantitatively decreased SV40 late gene expression in COS-1 cells. In contrast, competition with a plasmid containing SV40 nucleotides 1 through 294 (which removes all of T-antigen-binding site I and half of site II) was much less efficient. Finally, we demonstrated that in vivo competition experiments employing competitor fragments distal to the T-antigen-binding sites within the late template region (SV40 nucleotides 180 through 2533) resulted in superinduction of late gene expression in COS-1 cells. This finding suggests that negative factors such as repressors or attenuators may modulate late SV40 gene expression before induction. Our results are consistent with a model in which induction of late gene expression involves an interaction of the SV40 origin region with DNA-binding proteins, one of which may be T-antigen. Activation of the SV40 late transcription unit may involve induction of the SV40 enhancer or removal of a repressor-like protein or both.